Merambah Jalan Baru Studi Hadis: Tawaran Pendekatan Hermeneutika - Arifuddin Ahmad (Refleksi: Jurnal Kajian Agama dan Filsafat, 2005)
The presence of hadith in every human civilization demands a thorough ability to address every issue faced by the community. This is a dialectical consequence between the development of time and the demand to adhere to religious principles. However, striving towards this goal is not without obstacles, considering that the process of compiling hadith occurred thousands of years ago with multi-complex stages. Even though nowadays, the Prophet's Hadith can be easily traced in various authenticated books like the Kutub al-Sittah, this endeavor is not conclusive; many other important dimensions need to be understood. Hence, hermeneutical studies of hadith serve as a pathway to unravel the intricacies of the documented sayings, preserved over time.